Socioeconomic Impact of Covid-19 Pandemic in Africa: A Review of the Evidence (Lapai Journal of Economics, 2024)
This study analyzed the trend of Covid-19 and the socio-economic consequences caused by the pandemic on 54 African countries using the cross-sectional data of covid-19 update report of 1st and 11th November, 2020. The study employed descriptive statistical techniques, correlation as well as discourse analysis approach to analyze the impact of the pandemic on African countries. Although Africa has not been enormously affected in terms of the incidence and prevalence rates of the covid-19, the findings indicated that the pandemic had significant negative impact on various sectors of African economy notably aviation, education and health which consequently brought a serious setback in the overall growth and development in the region. Also, a strong correlation was found to exist between the number of covid-19 cases and deaths associated with the pandemic. This study therefore recommends for additional investment in the health sector in order to sufficiently equip healthcare centers with all necessary facilities to fast-track treatment process in time of emergencies. Also, the study calls for rigorous commitments on the part of governments to invest massively particularly in the highly affected sectors and come up with policies for ease of doing business in the region.